Evaluation of Interleukin-17A and Interleukin- 34 in Patients with Diabetic Foot Ulcer - Duaa M. Qasim; Abeer T. Al-Hasnawi; Masar R. Al-Mousawi; Akram A. Al-Abbadi (Karbala Journal of Medicine, 2025)
Background: Diabetic foot ulcers (DFU) are chronic complications of diabetes, characterized by poor wound healing, persistent inflammation, and increased risk of infection or amputation. Interleukin-17A (IL-17A) is a pro-inflammatory cytokine produced mainly by T helper 17 (Th17) cells. It helps fight bacteria and fungi, while Interleukin-34 (IL-34) modulates monocytes and macrophages through binding to the CSF-1 receptor. Both cytokines are associated with chronic inflammatory and autoimmune conditions. This study aimed to evaluate and compare the diagnostic value of IL-17A and IL-34 in DFU patients. Methods: A case-control study included 50 diabetic foot ulcer patients and 50 healthy people as a control group. Blood samples were collected for laboratory tests and to evaluate IL-17A and IL-34 serum levels in patients and controls using an enzyme-linked immunosorbent assay (ELISA) test. Results: Serum IL-17A and IL-34 levels were significantly higher in DFU patients compared to controls (P = 0.000 and 0.044, respectively). IL-34 showed better diagnostic performance with an area under the curve (AUC) of 0.743, sensitivity of 0.78, and specificity of 0.64 (P = 0.000). IL-17A demonstrated an AUC of 0.638, with lower sensitivity (0.32) and higher specificity (0.96) (P = 0.017). Conclusions: Both IL-17A and IL-34 levels were elevated in DFU patients. However, IL-34 demonstrated higher sensitivity and overall diagnostic accuracy, suggesting it may serve as a more reliable biomarker for early detection and diagnosis of diabetic foot ulcers. Keywords: Diabetic foot ulcer, IL-17A, IL-34, ELISA